Technology-Based Learning Policy Transformation: Evaluation of the Impact of Digital Platforms on Learning Effectiveness - Muh. Darwis; Aris Baharuddin; Oky Nur Pratiwi Johansyah (International Journal of Administration and Education (IJAE), 2025)
This research seeks to examine how the use of digital platforms influences the quality and effectiveness of learning, especially within the broader shift toward technology driven education policies. The study is grounded in a qualitative phenomenological design that prioritizes lived experiences and perceptions of participants. Through this approach, the research explores how digital platforms are incorporated into instructional practices and how they shape learning outcomes, including academic performance, levels of student participation, and the overall learning experience. Data were gathered by focusing on the perspectives of educators and learners who are directly involved in digital learning environments. Attention was given to daily teaching practices, patterns of interaction, and the ways digital tools support or hinder the achievement of learning objectives. The analysis reveals that digital platforms offer significant advantages, particularly in terms of learning flexibility, expanded access to educational resources, and opportunities for self-paced study. Learners can access materials beyond the constraints of time and place, while educators can diversify instructional strategies through multimedia and interactive features. The findings also highlight that these potential benefits do not automatically translate into effective learning. The success of digital platform implementation is strongly influenced by the availability and reliability of supporting infrastructure, such as internet connectivity, devices, and technical support. Equally important is the capacity of educators to redesign learning activities in ways that are pedagogically meaningful, rather than merely transferring conventional teaching methods into digital formats. Student readiness also plays a crucial role, including digital literacy skills, self-regulation, and motivation to engage in online learning. Overall, the study concludes that digital platforms can contribute positively to learning effectiveness when they are supported by adequate infrastructure and accompanied by thoughtful adaptation from both teachers and students. Without these conditions, the use of digital platforms risks becoming superficial and less impactful, limiting their contribution to meaningful learning improvement.